Analysis of the Influence of Financial Ratios on Profit Changes in Food and Beverage Subsector Companies Listed on the Indonesian Stock Exchange from 2018 to 2021 - Romauli Natalia Br Limbong; Afrida Yanti Siregar; Mohd. Nawi Purba (Kusuma Negara Business School, 2023)
The purpose of conducting this research is to test and analyze the effect of CR, QR, DER, DAR, TATO, ITO on changes in profits for food and beverage companies in 2018-2021. A total of 32 companies and 14 company samples were applied in this study, by applying quantitative methods and descriptive types with explanatory research in nature. Data was collected using the concept of documentation, in which the results of this study indicated that CR partially had no effect on changes in earnings with the results of multiple linear regression tests (tcount -1.174 < ttable 2.0095) with a significance value of 0.246 > 0.05. QR also has no effect on changes in profit with a value (tcount -0.043 < ttable 2.0095) accompanied by a significance of 0.966 > 0.05. DER has an effect on changes in profits with a value (tcount 6.981 > ttable 2.0095) accompanied by a significance of 0.000 <0.05. DAR has no effect on changes in earnings with a value (tcount -1.225 < ttable 2.0095) accompanied by a significance of 0.227 > 0.05. TATO has no effect on changes in earnings with a value (tcount 0.515 < ttable 2.0095) accompanied by a significance of 0.609 > 0.05. ITO has no influence on changes in profits with a value (tcount -0.766 < ttable 2.0095) accompanied by a significance of 0.447 > 0.05. Simultaneously CR, QR, DER, DAR, TATO, and ITO have an effect on changes in earnings accompanied by a significance of 0.000 <0.05.